2017
DOI: 10.1186/s40880-016-0172-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel germline mutations in FLCN gene identified in two Chinese patients with Birt–Hogg–Dubé syndrome

Abstract: Birt–Hogg–Dubé (BHD) syndrome, a hereditary renal cancer syndrome caused by mutations in the folliculin (FLCN) gene, is characterized by the presence of fibrofolliculomas, pulmonary cysts, spontaneous pneumothorax, and renal cell carcinoma (RCC). Few BHD syndrome cases have been reported in Asian countries, and cutaneous presentations are relatively rare in Asian patients. Asian BHD patients may be misdiagnosed due to their atypical manifestations. Here, we report two Chinese BHD patients with novel FLCN mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As the most serious clinical manifestation of BHD, screening for renal tumours at the time of diagnosis or from the age of 20 years is crucial to improve the prognosis. 48 However, only 9 patients 16 , 18 , 21 , 24 , 29 , 37 , 38 in our analysis who had a record age of diagnosis of renal cancer were also diagnosed with BHD within one year. Most of these patients were considered to have BHD because of pulmonary cysts or a history of pneumothorax on routine screening at the time of renal cancer surgery.…”
Section: Discussionmentioning
confidence: 72%
“…As the most serious clinical manifestation of BHD, screening for renal tumours at the time of diagnosis or from the age of 20 years is crucial to improve the prognosis. 48 However, only 9 patients 16 , 18 , 21 , 24 , 29 , 37 , 38 in our analysis who had a record age of diagnosis of renal cancer were also diagnosed with BHD within one year. Most of these patients were considered to have BHD because of pulmonary cysts or a history of pneumothorax on routine screening at the time of renal cancer surgery.…”
Section: Discussionmentioning
confidence: 72%
“…The 287 articles reviewed contain a total of 33 cases of childhood/adolescence pneumothorax in BHD (Bessis et al., ; César, Baudrier, Mota, & Azevedo, ; Chung, Ramos‐Caro, Beers, Ford, & Flowers, ; Demir & Cobanoglu, ; Ding et al., ; Furuya et al., ; Gunji et al., ; Gupta et al., ; Houweling et al., ; Johannesma, van den Borne, et al., 2014; Johannesma et al.,; Kolb, King, & Pearse, ; Kunogi et al., ; Li, Ning, He, & Gong, ; Maffe et al., ; Monserrate, Al‐Jaghbeer, & Cirino Marcano, ; Predina, Kotloff, Miller, & Singhal, ; So, ; Toro et al., ). Twelve of these 33 cases are described in case reports and the remaining 21 cases are reported as parts of larger cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, we encountered seven previous reports of SP in BHD at or below age 15 years. None of the large cohort studies describe more than one case of childhood pneumothorax each, regardless of potential selection bias (Li et al, 2017;Maffe et al, 2011). Only in the case series by Johannesma et al addressing specifically childhood pneumothorax in BHD, two incidences are reported (Johannesma, van den Borne, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1). Using the study criteria outlined above, 221 cases from 120 families with BHDS were included in the final analysis, which were reported in 20 papers (Table 1) [8][9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In 2008, the first 10 families with spontaneous pneumothorax and positive FLCN mutations in the Chinese population were described by a research team at Nanjing University [8].…”
Section: Demographic Datamentioning
confidence: 99%